On the joint estimation of multiple adoption decisions: the case of sustainable agricultural technologies and practices in Ethiopia - Hailemariam, T.; Kassie, Menale; Shiferaw, Bekele (2012)
Sustainable agricultural practices (SAPs) that lead to an increase in productivity are central to the acceleration of economic growth; this will alleviate poverty and help to overcome the recurrent food shortages that affect millions of households in Africa. However, the adoption rates of SAPs remain below expected levels. This paper analyzes the factors that facilitate or impede the probability and level of adoption of interrelated SAPs, using recent data of multiple plot-level observations. Multivariate and ordered probit models are applied to the modeling of adoption decisions by farm households facing multiple SAPs which can be adopted in various combinations. The results show that there is a significant correlation between SAPs, suggesting that adoptions of SAPs are interrelated. The analysis further shows that both the probability and the level of decisions to adopt SAPs are influenced by many factors: a household’s trust in government support, credit constraint, spouse education, rainfall and plot-level disturbances, household wealth, social capital and networks, including the number of traders known by a farmer in his vicinity, his participation in rural institutions, and the number of relatives he has inside and outside his village, labor availability, and plot and market access. These results imply that policy makers and development practitioners whose aims are to strengthen local institutions and service providers, maintain or increase household asset bases, and establish and strengthen social protection schemes, can speed up the adoption of SAPs.